2016
DOI: 10.1620/tjem.238.279
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms in the Apoptosis-Related Genes <i>TP63</i> and <i>CD40 </i>with Risk for Lung Cancer in a Chinese Han Population

Abstract: Apoptosis plays a critical role in tumorigenesis. TP63 inhibits the pro-apoptosis function of TP53, and CD40 increases expression of anti-apoptotic proteins. Two single nucleotide polymorphisms (SNPs), rs6790167 (g243059A>G) in intron 9 of TP63 and rs1535045 (g6194C>T) in intron 1 of CD40 respectively, may affect the susceptibility of lung cancer. To evaluate the association of these SNPs with lung cancer, we performed a case-control study with 258 patients, including 149 adenocarcinoma and 47 small cell lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These SNPs had been broadly researched in different genetic backgrounds. It turned out that rs1535045 had connection to many diseases, such as coronary artery calcification [23] and small cell lung cancer [11], and rs1883832 was related to systemic lupus erythematosus [24] and acute coronary syndrome [25].…”
Section: Discussionmentioning
confidence: 99%
“…These SNPs had been broadly researched in different genetic backgrounds. It turned out that rs1535045 had connection to many diseases, such as coronary artery calcification [23] and small cell lung cancer [11], and rs1883832 was related to systemic lupus erythematosus [24] and acute coronary syndrome [25].…”
Section: Discussionmentioning
confidence: 99%
“… 35 In a case-control study by Tang and colleagues (2016) genotyping SNPs of the intron 9 of TP63 rs6790167 (g243059A>G) in the non-smoking Chinese Han population, they found that the frequency of the CC genotype of rs1535045 was significantly higher in non-smoking lung cancer female patients, while the GG genotype of rs6790167 was significantly higher in non-smoking lung cancer male patients. 20 Lung cancer has the second-highest incidence among males and females, but there is a higher incidence among males, with a male-to-female ratio of 1.5–2.0. Interestingly, it has been noticed that lung cancer mortality is decreasing among males while it continues to increase among females.…”
Section: Molecular Differencesmentioning
confidence: 99%
“…In vivo studies have shown that the expression of CD40 is correlated with HPV positivity, vascular endothelial growth factor (VEGF) expression, and microvessel density [ 27 , 30 ]. In recent years, various studies have shown that CD40 gene polymorphisms are related to some malignant tumors, such as non-Hodgkin’s lymphoma [ 31 ], breast cancer [ 32 ], and lung cancer [ 33 , 34 ]. However, there were few reports on the relationship between the CD40 gene and cervical cancer [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%